POVERTY AND MARGINALIZATION OF THE ROMANI FAMILIES (Annual of the Faculty of Philosophy in Skopje, 2010)
The interest of this study is focused on a specific type of marginalization, at part of the Romani population in the Republic of Macedonia. The causes for their marginalization can be sought in the historical, cultural and social and economic context, accompanied with condition of poverty.The causes for their condition can be sought into:• Historical factors that have influenced the adaptation and integration degree of the Romani in the new cultural and social environments,• Cultural factors which are specific for this population,• Social and cultural factors which indicate the influence of the so- called “Romani occupations” based on their social and economic status,• Non-integration in the educational system, and• Lack of knowledge related to family planning.There by an attempt is made for explanation of the “magic circle” of the causative and consequential relations, between their marginalization and the condition of poverty.
Keywords: ROMANI; POVERTY; MARGINALIZATION